Assessing berry growth and quality in the context of a study on Grenache Noir irrigation for the production of Rosé wine - Hare, Thomas (2019)
Vinifera Euromaster - European Master of Science in Viticulture and Enology / Instituto Superior de Agronomia. Universidade de Lisboa / Montpellier SupAgro. Departement biologie - ecologie